2008
DOI: 10.1099/vir.0.83524-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies induced by the HA2 glycopolypeptide of influenza virus haemagglutinin improve recovery from influenza A virus infection

Abstract: The haemagglutinin (HA) of influenza A virus consists of two glycopolypeptides designated HA1 and HA2. Antibodies recognizing HA1 inhibit virus haemagglutination, neutralize virus infectivity and provide good protection against infection, but do not cross-react with the HA of other subtypes. Little is known regarding the biological activities of antibodies against HA2. To study the role of antibodies directed against HA2 during influenza virus infection, two vaccinia virus recombinants (rVVs) were used express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
47
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 22 publications
(20 reference statements)
3
47
0
1
Order By: Relevance
“…These results are in accordance with previous data on protective immunity induced by immunization with hA2, which was expressed by recombinant vaccinia viruses (Gocník et al, 2008) or E. coli (Bommakanti et al, 2010). In this work, we purified ehA2 according to chen et al (1995).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These results are in accordance with previous data on protective immunity induced by immunization with hA2, which was expressed by recombinant vaccinia viruses (Gocník et al, 2008) or E. coli (Bommakanti et al, 2010). In this work, we purified ehA2 according to chen et al (1995).…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, there are some regions of hA2 gp, which are conserved also among various subtypes (varečková et al, 2002, 2008). As we have shown previously, hA2 gp is immunogenic and able to induce a protective antibody response in mice (varečková et al, 2003a;Gocník et al, 2008). The most conserved part of hA2 gp is its n-terminus, FP.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Previous studies have suggested that HA2 could contain a potential epitope responsible for the induction of antibodymediated protective immunity (9). In the present study, a panel of MAbs against HA2 gp was characterized for their respective epitopes by epitope mapping.…”
mentioning
confidence: 99%
“…HA2 gp is a relatively conserved protein, and some HA2 epitopes are even shared among HA subtypes (Kostolanský et al, 2002;Varečková et al, 2008). HA2-specific antibodies recognizing HA stem were shown to be protective (Gocník et al, 2007(Gocník et al, , 2008Prabhu et al, 2009;Sui et al, 2009;Wang et al, 2010;Staneková et al, 2011;Janulíková et al, 2012), though they do not mediate virus neutralization by blocking the receptor-binding site on HA. We therefore suggest that anti-stem HA antibodies could help individuals exposed to dangerous avian IAV to overcome the infection in a subclinical manner.…”
Section: Discussionmentioning
confidence: 99%